More than data repositories: perceived information needs for the development of social sciences and humanities research infrastructures - Sendra, Anna; Late, Elina; Kumpulainen, Sanna (Information Research an international electronic journal, 2023)
Introduction. The digitalization of social sciences and humanities research necessitates research infrastructures. However, this transformation is still incipient, highlighting the need to better understand how to successfully support data-intensive research. Method. Starting from a case study of building a national infrastructure for conducting data-intensive research, this study aims to understand the information needs of digital researchers regarding the facility and explore the importance of evaluation in its development. Analysis. Thirteen semi-structured interviews with social sciences and humanities scholars and computer and data scientists processed through a thematic analysis revealed three themes (developing a research infrastructure, needs and expectations of the research infrastructure, and an approach to user feedback and user interactions). Results. Findings reveal that developing an infrastructure for conducting data-intensive research is a complicated task influenced by contrasting information needs between social sciences and humanities scholars and computer and data scientists, such as the demand for increased support of the former. Findings also highlight the limited role of evaluation in its creation. Conclusions. The development of infrastructures for conducting data-intensive research requires further discussion that particularly considers the disciplinary differences between social sciences and humanities scholars and computer and data scientists. Suggestions on how to better design this kind of facilities are also raised.